Competencies of Bachelor of Science in Office Administration Students in Machine Shorthand - Balbuena, Christine Mae P.; Baladia, Bernadette B.; Lascano, Hannah Mikaela O.; De Loyola–Lagatic, Alyssa Florese (Journal of Organizational and Human Resource Development Strategies, 2025)
This study focused on the Competencies of Bachelor of Science in Office Administration Students in Machine Shorthand, it sought to identify: profile of the respondents in terms of age, sex and year level, competencies of BSOA students in machine shorthand in terms of dictation and transcription, challenges of BSOA student in machine shorthand in terms of dictation and transcription, as an output of this study an intervention plan than was proposed to enhance the competencies of BSOA student in machine shorthand. The respondents of this study were the BSOA students, composed of the 2nd year and 3rd year students in the Bachelor of Science in Office Administration for the academic year 2023-2024, with a total of 100 respondents. This study utilized the Quantitative Descriptive Research Method and percentage technique, weighted mean, and rank order method as the statistical tools. The study revealed that, in terms of Personal Profile, the majority are 19-20 years old, the majority are female, and the majority of the respondents are 3rd year students. In conclusion, the competencies of Bachelor of Science in Office Administration Students in Machine Shorthand in terms of the competencies of BSOA Students in terms of transcription and dictation were found to be competent. Challenges of BSOA Students in Machine Shorthand in terms of Transcription and Dictation were found to be Often Encountered. The output of this study is the proposed recommendation to enhance the Competencies of Bachelor of Science in Office Administration Students in Machine Shorthand.